2017
DOI: 10.1002/clc.22692
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of REDUCE‐IT: Reduction of Cardiovascular Events with Icosapent Ethyl–Intervention Trial

Abstract: Residual cardiovascular risk persists despite statins, yet outcome studies of lipid‐targeted therapies beyond low‐density lipoprotein cholesterol (LDL‐C) have not demonstrated added benefit. Triglyceride elevation is an independent risk factor for cardiovascular events. High‐dose eicosapentaenoic acid (EPA) reduces triglyceride‐rich lipoproteins without raising LDL‐C. Omega‐3s have postulated pleiotropic cardioprotective benefits beyond triglyceride‐lowering. To date, no large, multinational, randomized clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(146 citation statements)
references
References 33 publications
5
136
0
5
Order By: Relevance
“…Unique identifier: NCT01492361) is expected to be the first of these trials to present results, which are expected in the second half of 2018. This phase 3b, international, multicenter, prospective, double‐blind, placebo‐controlled, parallel‐group trial randomized ≈8000 high‐risk patients receiving stable statin therapy with triglycerides 1.69 to 5.64 mmol/L (150–499 mg/dL) to the highly purified omega‐3 fatty acid icosapent ethyl (ethyl ester of eicosapentaenoic acid) 4 g/d or matching placebo 33. Patients in this trial are required to have a history of cardiovascular disease or diabetes mellitus plus an additional cardiovascular risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Unique identifier: NCT01492361) is expected to be the first of these trials to present results, which are expected in the second half of 2018. This phase 3b, international, multicenter, prospective, double‐blind, placebo‐controlled, parallel‐group trial randomized ≈8000 high‐risk patients receiving stable statin therapy with triglycerides 1.69 to 5.64 mmol/L (150–499 mg/dL) to the highly purified omega‐3 fatty acid icosapent ethyl (ethyl ester of eicosapentaenoic acid) 4 g/d or matching placebo 33. Patients in this trial are required to have a history of cardiovascular disease or diabetes mellitus plus an additional cardiovascular risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger evidence is needed. In addition to the REDUCE‐IT study, the Outcomes Study to Assess Statin Residual Risk Reduction With EpaNova in High CV Risk Patients With Hypertriglyceridemia (STRENGTH) and the Pemafibrate to Reduce Cardiovascular Outcomes by Reducing Triglycerides In Patients With Diabetes (PROMINENT) studies are ongoing large CV outcomes trials involving high‐risk CVD patients, including a large percentage of patients with diabetes, undergoing statin therapy, with the results from the REDUCE‐IT study (EPA vs placebo) to be presented first in 2018 …”
Section: Discussionmentioning
confidence: 99%
“…The 2 trials that suggested benefits of omega‐3 FA supplementation enrolled older patients (average age of 60) and focused only on clinical outcomes as opposed on patient‐reported outcomes . Another 3 clinical trials of omega‐3 FA supplementations are currently ongoing, which are also focusing on older patients . A recent American Heart Association Advisory report recommends replacement of saturated fat with polyunsaturated vegetable oils that consist of high omega‐6 linoleic acid to lower cardiovascular disease risk, largely based on evidence from middle‐aged and elderly population .…”
Section: Discussionmentioning
confidence: 99%